Faktor Yang Mempengaruhi Capital Structure Pada Sektor Industri Dasar Dan Kimia - Lie Sha, Thio (Jurnal Ekonomi, 2019)
The purpose of this study is to obtain empirical evidence about the effects  of  business risk, profitability, firm size, asset structure, and growth of asset to capital structure in the company's manufacturing base and chemical industry sectors listed on the Indonesia Stock Exchange during 2011-2014. The total sample is 80 samples obtained by purposive sampling method. Data analysis was done using  multiple linear regression method with SPSS software 20 version.  The result based on t test indicate  that  business risk, firm size,  asset structure, and  asset growth of the company has positif and significant influence on struktrur capital., profitability has negatif  and  significant influence on struktrur capital.  F-test results showed that the variable business  risk, profitability, firm size, asset structure and asset growth together have a significant effect on the capital structure.